Synthesis, Characterization and Antibacterial Activity of Co(II), Cu(II) and Zn(II) Complexes Derived from 4-Methylthiosemicarbazide and 5-Nitrosalicylaldehyde - Zhang, Gai; Li, Yingying; Feng, Xun; Zhang, Ronglan; Zhao, Jianshe (Asian Journal of Chemistry, 2012)
The reaction of cobalt(II), copper(II) and zinc(II) with NS donor ligand derived by condensing 5-nitrosalicylaldehyde with 4-methylthiosemicarbazide have been carried out. The structure of the NS donor ligand was determined by single-crystal X-ray diffraction analysis. The crystal belongs to monoclinic system, space group C2/c, with cell parameters: a = 1.31165(5), b = 0.71876(3), c = 2.38370(7) nm, a = 90º, b = 90.855º(3), g = 90º, V = 2.24701(14) nm3, Z = 8, F(000) = 1056, Mr =254.27, Dc =1.503 g/cm3, μ(MoKa) = 0.291 mm-1, R1 = 0.0462, wR2 = 0.1202. The analysis of the crystal structure indicates that the complex has a three-dimensional network structure, which is formed by hydrogen bonds and electrostatic interaction. The ligand and its metal complexes are determined by elemental analysis, infrared spectra, UV spectra and the antibacterial activity. It is concluded that the thionic sulphur and Shiff base nitrogen atom of ligand are bonded to the metal ion. The results of antibacterial activity show that all of the ligand and the complexes can restrain the activity of bacteria.